PHYSICAL, THERMAL AND TENSILE ANALYSIS OF SANSIVERIA ROXBURGHIANA LEAF FIBER. Issue 14 (28th October 2022) - E, Devaki; Boominathan, Senthilkumar
ABSTRACT: In this research work, the fibers were extracted from the leaf of the Sansevieria roxburghiana plant through a mechanical decortication process. The morphological structure of the fiber was analyzed using a scanning electron microscope and optical microscope. The chemical composition and crystallinity of the fiber were analyzed using Fourier transforms infrared, and X-ray diffraction techniques. The physical and tensile properties of the fibers were measured and compared with the cotton, sisal, and other varieties of sansevieria fibers. The average length of the fiber was around 7.6 cm and the density of the fiber was found as 1.41 g/cc. The thermal properties of the fiber were analyzed using Thermogravimetric (TGA) analysis. TGA tests showed that the fiber is stable below 220 ◦ C temperature. The crystallinity of the fiber was measured as 46.42%. It is understood that Sansevieria roxburghiana can be suitably considered to use as reinforcement in green composite materials and other technical textiles sectors.